Intergenerational Scars: The Impact of Parental Unemployment on Individual Health Later in Life - Michele Ubaldi; Matteo Picchio (Institute of Labor Economics (IZA), 2023)
This paper studies whether individuals that experienced parental unemployment during their childhood/early adolescence have poorer health once they reach the adulthood. We used data from the German Socio-Economic Panel from 2002 until 2018. Our identification strategy of the causal effect of parental unemployment relied on plant closures as exogenous variation of the individual labor market condition. We combined matching methods and parametric estimation to strengthen the causal interpretation of the estimates. On the one hand, we found a nil effect for parental unemployment on mental health. On the other hand, we detected a negative effect on physical health. The latter is stronger if parental unemployment occurred in early periods of the childhood, and it is heterogeneous across gender. The negative effect of parental unemployment on physical health may be explained by a higher alcohol and tobacco consumption later in life.
Keywords: I14; J13; J62; J65; 330; parental unemployment; plant closure; mental health; physical health; health behaviors